PENANAMAN NILAI-NILAI IMAN KRISTEN MELALUI KEGIATAN KEROHANIAN DI PANTI ASUHAN SALIB PUTIH SALATIGA - Yozabad Bagas Ady Kristianto; Yonatan Yakub Mononimbar; Paulus Karaeng Lembongan (SAGACITY : Journal of Theology and Christian Education, 2020)
The aim of this study is to describe the means to how Christian faith values is being taught through spiritual activities at Salib Putih Orphanage Salatiga. Data gathering was conducted through interviews, observations, and the results of the study were analysed qualitatively. Social orphanages function is to replace the role of parents in nurturing. This is the starting point for orphans to form their identity. Orphanages can also be regarded as a place for them to survive and grow. The inculcation of Christian faith values in children aims to equip foster children with faith towards God, spiritual maturity, virtuous characters and to restore their identity.